Financial market reaction to cyberattacks - Niaz Kammoun; Ahmed Bounfour; Altay Özaygen; Rokhaya Dieye (Cogent Economics & Finance, 2019)
Drawing upon an extensive dataset comprising 3,680 cyberattacks on firms listed in 5 stock markets, our main objective is to ascertain the financial market reaction based on a hybrid valuation inspired by the event study methodology and a counterfactual analysis. Analyses concern three dates that are specific to cyberattacks: 1) the accident date; 2) the first notice date; and 3) the original loss start date. Results indicate that there is a negative abnormal return for the NASDAQ after the accident date. The reactions of the NASDAQ and NYSE are similar, and negative for the first notice date but positive after the original loss start date. In the European context, cumulative abnormal returns are negative for French and German companies after the first notice date.
Keywords: G11; G14; G15; G22; 330; Cyberattacks; valorization; market sensitivity; event study methodology; cumulative average abnormal return; counterfactual analysis